2017
DOI: 10.1080/10942912.2017.1362650
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profile and biological activities ofMicromeria graeca(L.) Benth. ex Rchb.

Abstract: The medicinal potential of the ethanol extract of Micromeria graeca (L.) Benth. ex Rchb., harvested in Algeria (MG extract), was evaluated by assessing in vitro its antioxidant, antibacterial, and antityrosinase properties. The total phenolic (= 430 ± 30 mg gallic acid equivalent/100 g of dry weight) and flavonoid (= 190 ± 10 mg quercetin equivalent/100 g of dry weight) contents were evaluated by the Folin-Ciocalteu and the aluminium chloride methods, respectively. Silica gel thin-layer chromatography revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Emulsification of LA in PB 20 mM pH 7, using Tween-20 (5.6 µg/mL LA and 5.6 µg/mL Tween-20) Mixture of emulsion in PB, water and sample dissolved in 80% methanol [70] Dissolution of LA (8 mM) in Borate buffer 50 mM pH 9 Mixture of previous solution with FeSO 4 , EDTA, H 2 O 2 , sample dissolved in methanol and PB 0.4 M pH 6.75 [126] Dissolution of sodium linoleate in water (16 mM) Mixture of previous solution in PB 50 mM pH 7.4 [127] Dissolution of LA in ethanol, 2.5% (v/v) Mixture of previous solution with distilled water, PB 50 mM pH 7 and sample [74] Ethanol Dissolution of LA (1.3% (v/v)) and NP in ethanol:water 3:1 (v/v) [76] Different methods available to disperse linoleic acid in a medium that is compatible with oxidizing conditions allow the adaptation of the medium for NP dissolution. For instance, the work of Freitas et al [76] used a system mostly composed of ethanol, which might allow the LPIP determination of a wider range of NPs (including some less polar extracts) using water-soluble radical initiators (such as AAPH) or transition metals.…”
Section: Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Emulsification of LA in PB 20 mM pH 7, using Tween-20 (5.6 µg/mL LA and 5.6 µg/mL Tween-20) Mixture of emulsion in PB, water and sample dissolved in 80% methanol [70] Dissolution of LA (8 mM) in Borate buffer 50 mM pH 9 Mixture of previous solution with FeSO 4 , EDTA, H 2 O 2 , sample dissolved in methanol and PB 0.4 M pH 6.75 [126] Dissolution of sodium linoleate in water (16 mM) Mixture of previous solution in PB 50 mM pH 7.4 [127] Dissolution of LA in ethanol, 2.5% (v/v) Mixture of previous solution with distilled water, PB 50 mM pH 7 and sample [74] Ethanol Dissolution of LA (1.3% (v/v)) and NP in ethanol:water 3:1 (v/v) [76] Different methods available to disperse linoleic acid in a medium that is compatible with oxidizing conditions allow the adaptation of the medium for NP dissolution. For instance, the work of Freitas et al [76] used a system mostly composed of ethanol, which might allow the LPIP determination of a wider range of NPs (including some less polar extracts) using water-soluble radical initiators (such as AAPH) or transition metals.…”
Section: Watermentioning
confidence: 99%
“…For instance, the work of Freitas et al [76] used a system mostly composed of ethanol, which might allow the LPIP determination of a wider range of NPs (including some less polar extracts) using water-soluble radical initiators (such as AAPH) or transition metals. In more aqueous systems, the use of saponified linoleic acid (the sodium salt, for instance) to increase water solubility, with [70,73,128] or without [70,126] the addition of a surfactant, might be a solution to test very hydrophilic compounds (such as natural polysaccharides), which are insoluble, even at low concentrations of organic solvents.…”
Section: Watermentioning
confidence: 99%
“…Non L., M. fruticosa (L.) Druce) are well known to contain essential oil and flavonoids [ 36 ]. Brahmi et al observed antibacterial activity of the Micromeria extract against four pathogenic bacteria, E. coli ATCC 25922, P. aeruginosa ATCC 9027, S. aureus ATCC 6538, and S. aureus 100459, the extracts were inactive against all test-microorganisms (MIC ˃ 2000 μg/mL) [ 18 ]. Ali-Shtayeh et al reported that the freeze-dried water extract of M. nervosa (Desf.)…”
Section: Resultsmentioning
confidence: 99%
“…(origin, Palestine) indicated lowest activity [ 19 ]. According to Brahmi et al nonpolar extracts from plants have been shown more effective antibacterial properties than polar extracts [ 18 ]. Despite the high polyphenol and flavonoid content (26,570.5 ± 291.3 mg/100 g DW and 1564 mg/100 g DW, respectively) of the used extract, we detected antimicrobial activity against only one foodborne pathogen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation